Conserving and sustaining culture through Sarawak traditional Malay woman headscarves / Awang Rozaimie - Rozaimie, Awang; Bolhassan, Rashidah; Abdullah, Regina Garai; Johari, Aiza (Universiti Teknologi MARA Cawangan Sarawak, 2020)
The traditionally Sarawak Malay woman headscarf is known as Tudong Selayah Keringkam. It is a hand-made identical embroidery headscarf, produced with articulate skills, creativity, and imagination and worn as a social identity among the Malay women in Sarawak. This paper argues that the Selayah and the Keringkam are two different pieces of headscarves artwork. This paper also foresees the reasons behind the depletion of interest and skills of producing this artifact among the younger generation, to a large extent, making the cultural sustainability of the traditional headscarves in Sarawak to become less significant. Hence, the objectives of this paper are to explore the distinction between Selayah and Keringkam. In this transcendental phenomenological paper, the ‘framing approach’ is used in the in-depth interviews conducted with Selayah Keringkam weavers and Malay elders. This paper apparently has found the little provision to the distinction between Selayah and Keringkam. However, there are five elements posited which have contributed to the depletion of interest among the young generation in the production of Selayah Keringkam. Those elements are labelled as Price, Realism, Technology, Proficient and Insight. Nonetheless, this paper is significant in highlighting the Selayah Keringkam as one of the key material cultures in sustaining Sarawak Malay heritage. Preserving and sustaining the social identity is crucial which potentially becomes central to the tourism products and commercially plated onto the international arena of fashion, art, and design.